Solving challenges in an electronic banking services company by implementing enterprise architecture 252 frameworks / Thanyatida Gunadham and Eiman Mustafa Ahmed Mohammed - Gunadham, Thanyatida; Ahmed Mohammed, Eiman Mustafa (Faculty of Information Management, 2022)
Enterprise architecture has always been important for the business. It helps to close the communication gaps between stakeholders and provides a better understanding of the different roles and responsibilities of the stakeholders. Businesses can gain a competitive advantage from implementing enterprise architecture. Various types of businesses have implemented enterprise architecture. The electronic banking business is one of them. The article aims to discuss the challenges that an electronic banking services company faces and how these challenges can be solved by implementing the enterprise architecture framework. Several challenges have been addressed such as no clear boundaries between departments, duplicated projects, delays in the process flow, and no standard method for documentation. These challenges should be solved by implementing enterprise architecture frameworks, namely the Zachman framework and TOGAF.